Kebersyukuran dan ketangguhan sebagai mediator dukungan sosial dengan kesejahteraan psikologis guru honorer: Gratitude and resilience as mediators of social support with psychological well-being of honorary teachers - Pambuka, Fian Rizkyan Surya; Lestari, Sri (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
According to the Organisation for Economic Co-operation and Development (OECD) 2023, teacher salaries in Indonesia are quite low. The problem of low compensation for honorary teachers has an impact on job satisfaction and reduces the psychological well-being of honorary teachers. This study aims to examine the psychological well-being model of honorary teachers. This study uses a quantitative approach with a survey design. The instruments used are the Ryff Psychological Well-being Scale, Social Support Scale, Gratitude Scale, and Short Grit Scale. This study involved 334 honorary teachers who were taken using the convenience sampling technique. Data were analyzed using path analysis techniques with the help of the SEM-PLS program. The results of the study showed that social support has an indirect effect on the psychological well-being of honorary teachers through gratitude and resilience. This study concludes that the availability of social support is not enough to make honorary teachers achieve psychological well-being. Honorary teachers need an attitude of gratitude and resilience in order to be psychologically prosperous. This study implies that it is necessary to develop a training program to increase gratitude and resilience so that teachers achieve psychological well-being.